COMMUNITY-BASED COUNSELING TO MITIGATE SOCIO-ECONOMIC IMPACTS OF MARINE SEDIMENT CLEANING IN KARIMUN REGENCY - Sitinjak, Theresia; Ramdani, Ramdani; Ahmad, Yanizon; Marpaung, Junierissa; Soeboer, Deni Achmad (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2025)
The use of marine sediments in Karimun Regency causes socio-economic changes that have a direct impact on the psychological well-being of students in coastal areas. This study aims to formulate the design of collaborative guidance and counseling services as a mitigation strategy for family pressure, income instability, and community social dynamics arising from sediment extraction activities. Qualitative research methods were used to analyze contextual data, empirical literature, and school service needs. The results of the study show that these socio-economic impacts contribute to increased stress, decreased learning motivation, and behavioral vulnerability in students. These findings underscore the need for a collaborative guidance and counseling services model that integrates data mapping, cross-agency partnerships, family and community-based psychosocial interventions, and environmental-social literacy education. The formulated model positions counselor as systemic links between schools, families, and coastal stakeholders, thereby strengthening student resilience and increasing the effectiveness of services in the context of ecological and socioeconomic changes